Friction Characteristics of Machined Metal with Different Surface Morphologies - Hsin-Min Lee; A-Cheng Wang; Yan-Cherng Lin (Advances in Materials Science and Engineering)
This study examined the friction characteristics of SAE1045 medium carbon steel processed by milling machining (MM) and abrasive jet machining (AJM). Friction experiments were conducted with variations in load and friction distance. Experimental results show that micro craters produced by AJM help retain lubricant on workpiece surface and thus decrease friction coefficient. Consequently, for the same friction distance, the amount of wear on AJM test specimens is less than that of MM ones. Moreover, increase in load and surface roughness will also result in great wear on the test specimens.